Web-Based Population Administration Information System at Sidokumpul Village - Muhammad Faris Afif Putra; Bonda Sisephaputra (Universitas Negeri Surabaya, 2026)
Population administration services in Sidokumpul Village are predominantly managed through conventional manual procedures, resulting in long administrative queues, service delays, accumulation of physical documents, and limited access to information for residents. These challenges indicate the need for a digital solution that can improve efficiency, accuracy, and accessibility of population administration services at the village level.